A randomized observational study into the pattern of hearing loss in chronic suppurative otitis media - Gupta, Sucheta; Gupta, Vinod (International Journal of Clinical Trials, 2022)
Background: Chronic suppurative otitis media (CSOM) is an important and a highly prevalent disease of the middle ear and poses serious health problem worldwide especially in developing countries. The objective of the current study was to evaluate the association between CSOM and sensorineural hearing loss (SNHL) and to study of pattern of hearing loss and clinical factors and demographic variables, if any, that might affect sensorineural component, in CSOM in North-Indian population. Methods: A randomized observational study was conducted on 120 patients, in the age-group of 1 to 50 years, divided into two groups of 60 each: who had safe CSOM and unsafe CSOM, over a period of 6 months, i.e., from: July 2021 to December 2021, in the department of otorhinolaryngology and head neck surgery, CHC, Chenani, Udhampur, J and K, India. Results: Out of 60 patients under safe CSOM, Male: Female ratio stood at 1:1.14 (i.e., 28:32). Mean duration ± SD of the disease stood at: 6.2±5.09 years. Incidence of hearing loss was observed in 93 (77.5%) patients of conductive type and 27 (22.5%) patients of mixed type and 19 patients (31.67%) were of unsafe mixed type. Maximum incidence of 35% was in the age group of 41-50 years and minimum in 11-20 years i.e., 7.32%. Total incidence of SNHL 16.67%. Conclusions: A significant association between SNHL and CSOM was found in this study, with incidence of SNHL increasing with advancing age, showing that age as a risk factor for sensorineural component of hearing loss in CSOM.